PENGARUH KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN CONSIGNMENT PADA PT.MATAHARI DEPARTMENT STORE DI PLAZA MULIA SAMARINDA - Suci Amala (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2021)
Organizational commitment are important for companies who want to improve employe performance. PT. Matahari Department Store Plaza Mulia Samarinda is a branch of PT. Matahari Department Store, tbk which is distributedin several parts of Indonesia. PT. Matahari Department Store is a company that’s sells a wide variety of fashion needs ranging from clothing for children to adult, shoes, slippers, beauty products, accessories, children’s toys to household needs. This research aims to determine the influenceof organizational commitment to the consignment employee performance of PT. Matahari Department Store Plaza Mulia in Samarinda. The organizational commitment (X) are used as independent variables while the employee performance as dependent variables. Primary data is obatained by conducting interviewsto 57 respondent using questionnaris. Secondary data is obtained by conducting field observation. Analysis data uses a simple linear regression technique with SPSS 22 software. The result showed that the organizational commitment variables (X) significantly influence to employee performance (Y) PT. Matahari Department Store Plaza Mulia in Samarinda. Suggestions for PT. Matahari Department Store Plaza Mulia in Samarinda the company should build an emotional bond, convince employees to last long in company, make employees aware that leaving the company will harm the employees themselves, pay attention to loyalty outside the working hours that have been given by employees in order to reduce the level of permits or delays.